La Constelación S: Subyugación, Sacrificio y Salvación - Sandra López (Convergencia, 2005)
In this article I will return to the experience of the investigation The Effects of the Conflict on Colombian Womens Lives and Their Forms of Resistance, conceived and carried out for the Colombian Womens Peace ful Way, La Ruta Pacífica, between june 2003 and march 2004. This investigation was carried out in the Departments of Cauca, Putumayo and Chocó, and in the city of Medellín. The objective of the article is to show that the Constellation : Subjugation, Sacrifice and Salvation have been a cultural construction and that their ef fects are intensified in the context of armed conflict. It will discuss some of the relationships between the private and the public, tradition, the present and the conflict